Digital Competence and Lecturer Performance: The Roles of Digital Teaching Innovation and Organizational Support - Rasyid, Rohsita Amalyah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The massive digital transformation has fundamentally altered the higher education landscape, compelling lecturers to adapt by integrating advanced technologies into their daily teaching practices. A primary challenge faced by Private Universities, particularly in developing regions, is ensuring that the digital competence possessed by lecturers is effectively translated into relevant and high-quality teaching performance. This study aims to empirically examine an integrative model linking digital competence to lecturer performance, mediated by digital teaching innovation and moderated by the role of organizational support. Employing a quantitative explanatory research design, data were collected from 210 lecturers across various Private Universities in Kendari City through structured questionnaires. Data analysis was conducted using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) to test the proposed hypotheses. The results provide empirical evidence that digital competence exerts a positive and significant influence on both teaching innovation and lecturer performance. Specifically, digital teaching innovation proves to be a vital mediator that bridges the gap between individual technical capabilities and tangible classroom outcomes. Furthermore, a crucial finding of this study is that organizational support positively moderates (strengthens) the relationship between digital competence and performance. This indicates that lecturer performance reaches its optimal level only when individual competencies are backed by an institutional environment that provides adequate facilities and supportive policies.